Writing Toward the Word: Deconstruction and Negative Theology in Samuel Beckett's The Unnamable - Abma, Annette (My University, 1992)
This study examines Samuel Beckett's The Unnamable with respect to deconstructive literary theory and negative theology, exploring a possible homology between these two discursive stategies. My reading involves a three-part investigation into Beckett's text as an aporetic discourse which simultaneously promises "meaning" while rendering such "meaning" impossible. The study begins with a close examination of indexical forms of language which serve to dislocate the speaking subject. In order to situate the Unnamable, I undertake an examination of the narrator's "position" with respect to the Mahood/Worm, I/not-I opposition in which each figure acts as a supplement for the Unnamable. My second reading moves beyond the question of the subject to a question of language's play. This chapter is largely theoretical, examining the indexical language of time and space in The Unnamable with respect to Derridean terms such as différance, bricolage and the supplement. The third chapter involves an exploration of the theological possibilities and impossibilities effected by the "concept" of différance as a possible "name" for the Unnamable as well as the "God" of negative theology. This final reading studies The Unnamable as anti-theological in its resistance to a totalizing ground or presence, yet theo-logical in that it does not deny a belief or faith in an innocent and unnamable "God". My motivation is that writing is always a writing towards the Word which writing always already displaces and defers.
Keywords: English Language and Literature; English Language and Literature